Sociocultural and Ecological Dynamics of Green Spaces in Brazzaville (Congo). (1st March 2020) - Kimpouni, Victor; Nzila, Jean De Dieu; Watha-Ndoudy, Noël; Kokolo Bilongo, Elodie Charleine; Yallo Mouhamed, Salisou; Kampe, Jean-Pierre; Louembe, Dieudonné
Abstract : The study was conducted in Brazzaville, and data collection covers the period from May to June 2017. The methodology is based on literature review and floristic and equipment inventory. Nine green spaces spread over two out of nine townships in the capital city. Four are located in Bacongo and five in Poto-Poto. According to the classification standards, 5 squares and 4 gardens were studied. Except for one square, all the others, including the gardens, are planted with trees. The equipment inventory lists 183 benches, including 63.83% permanently and/or partially in the sun, 4 playgrounds, no games for children, and 3 cultural monuments. The flora and health of the trees stands shows 186 trees and 279 shrubs, all corresponding to 26 species. An examination of the health status reveals that 57% of trees show anthropogenic injuries. Floral analysis shows that exotic plants (76.92%) predominate over local plants (23.07%). The average basal area of trees in all green spaces is 1.95 m 2 ·ha −1 . The diametric structure is erratic within all green spaces, with a dominance of large diameter subjects. This leads to poor natural regeneration of woody plants. The green spaces in Brazzaville, which are very unevenly distributed within the urban fabric, do not meet the international standards disseminated by the World Health Organization (WHO) and do not fully play their biodiversity conservation and recreational and ecological functions. History of green spaces in Brazzaville states that no creation was born after independence. The existing land has been reduced in size, and the new land has been used for other purposes.